2010
DOI: 10.1080/09737766.2010.10700893
|View full text |Cite
|
Sign up to set email alerts
|

Web Presence of Selected Asian Countries: A Webometric Study

Abstract: The paper focuses on the Web presence and visibility of Asian countries websites. The paper tries to highlight the Web presence using some webometric indicators like Internet access, webpages, number of Internet users, and link studies. The study analyzes the web presence using popular search engines like Altavista, Google, Yahoo and MSN. An attempt has also been taken to find out the Web Impact Factor (WIF) for selected Asian countries. The result shows that China (43.7%), Japan (16.7%) and India (10.4%) occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A webpage is a "page" of the World Wide Web (WWW), usually in HTML format and with hypertext links, to enable navigation from one page or section to another page (Zhu, et al 2007). Website page size is the size of Specific Uniform Resource Locator (URL) (Jalal, et al 2010).…”
Section: Top-level Domain Webpage and Webpage Sizementioning
confidence: 99%
“…A webpage is a "page" of the World Wide Web (WWW), usually in HTML format and with hypertext links, to enable navigation from one page or section to another page (Zhu, et al 2007). Website page size is the size of Specific Uniform Resource Locator (URL) (Jalal, et al 2010).…”
Section: Top-level Domain Webpage and Webpage Sizementioning
confidence: 99%
“…2006) conducted a study on collaboration analysis of 38 world national library websites via webometric methods and found that the United States of America, Australia and United Kingdom were the popular and most visible national library websites. Jalal et. al.…”
Section: Brics Countriesmentioning
confidence: 99%
“…Therefore, university authority may give proper care for the upliftment of their existing ranking not only at the national level but also at the global level. Few studies on ranking of Indian universities 10 and Asian countries 11 , African countries, Australian countries, European countries were conducted so far. Besides, national as well as global ranking system has emerged and few notable ranking systems are: Ranking Web of World Universities (RWWU), Shanghai Ranking, Times Higher Education (THE), 4 International and College Universities (4ICU), etc.…”
Section: Literature Reviewmentioning
confidence: 99%